Persepsi Konsumen Produk Teri Crispy Kampung Nelayan Maju di Kota Samarinda - Ayuni Ayang Kumara; Fitriyana Fitriyana; Etik Sulistowati Ningsih (JURNAL RISET RUMPUN ILMU HEWANI, 2023)
This research was conducted with the aim of understanding Consumer Perception of Crispy Anchovy Products from the Fishing Village of Maju Rawa Makmur, Palaran Subdistrict, Samarinda City. The research was carried out in the Fishing Village of Maju Rawa Makmur, Palaran Subdistrict, Samarinda City. The sampling methods used were purposive sampling and accidental sampling with 25 consumers. The data analysis method used was qualitative analysis, which is structured, focused, and specific, yet flexible and subject to change as needed.Based on the research findings, it was found that concerning the taste of crispy anchovies, the majority of consumers (80%) rated it as "quite liked," indicating that most consumers find the taste of crispy anchovies to be quite enjoyable, with only a small portion finding it very delicious. Regarding the color of crispy anchovies, the majority of consumers (84%) rated it as "quite liked," suggesting that most consumers have a positive view of the product's color. As for the packaging of crispy anchovies, the majority of consumers (84%) rated it as "quite liked," showing that most consumers find the product's packaging to be quite good, with a small portion finding it very good. Regarding the price of crispy anchovies, the majority of consumers (76%) rated it as "liked" or even "very liked," indicating that most consumers have a positive view of the product's price. Although there is a small portion that only finds it "quite liked," the satisfaction level with the price appears to be relatively high based on consumer evaluations.